Essential type : an illustrated guide to understanding and using fonts - Seddon, Tony, 1965- (New Haven, CT : Yale University Press, 2016)
"Have you ever wondered which typeface is used for airport signs? Or about the history behind the Times New Roman font? We are constantly engaging with type, yet many of us struggle to use it effectively or simply to understand the basics. This beautifully illustrated, easy to use companion is the perfect guide to everything typographic. Tony Seddon provides an essential lexicon that explains the history and functionality of 140 type terms and 20 unique typeface classifications. The book also features a timeline of typeface classification from the mid-15th century to the present day, and concludes with a chapter detailing over 40 important typeface families that reflect the history of typeface development and typographic style from the earliest days of movable type. Essential Type will help to build your knowledge of type and typeface use with a clear and comprehensive "what is it" and "why use it' approach to the subject. Five chapters explore topics including the anatomy of type, glyphs, typeface classification, and typefaces ranging from serif to sans serif to script and display. The chapter on typefaces pays particular attention to highlighting key design features and, along with illuminating backstories and tips to aid identification, makes this book the perfect companion for all type enthusiasts and practitioners." -- Publisher's description
Chapter 4: Type Classifications. Ancient; Blackletter; Humanist Serif; Old Style Serif; Transitional Serif; Rational Serif; Formal Script; Casual Script; Grotesque Sans; Grotesque Slab; Geometric slab; Humanist Slab; Gothic Sans; Geometric Sans; Humanist Sans; Neo-Grotesque Sans; Neo-Humanist Sans; Glyphic; Contemporary Serif; Display -- Chapter 5: The Typefaces. Jenson; Bembo; Garamond; Caslon; Baskerville; Bodoni; Century; Copperplate Gothic; Goudy Old Style; Perpetua; Joanna; Times New Roman; Sabon; Swift (Neue Swift); Brioso; Clarendon; Rockwell; PMN Caecilia; Archer; Wilhelm Klingspor Schrift; Bickham Script; Suomi Hand Script; The Carpenter; Akzidenz-Grotesk; Franklin Gothic; News Gothic; Futura; Gill Sans; DIN; Folio; Univers; Helvetica; Optima; ITC Avant Garde Gothic; Frutiger; Avenir; ITC Officina Sans; Gotham; Cooper Black; ITC Bauhaus; Trajan; Lust; Lulo -- Useful shortcuts.
Includes bibliographical references (page 187) and index.
Keywords: Type and type-founding.; Graphic design (Typography)